Clandestine abortion causing uterine perforation and bowel infarction in a rural area: a case report and brief review. (December 2016) - Sama, Carlson; Aminde, Leopold; Angwafo, Fru
Abstract Background An unsafe abortion is defined as a procedure for terminating an unintended pregnancy carried out either by a person lacking the necessary skills or in an environment that does not conform to minimal medical standards or both. Majority of these unsafe abortions are carried out in rural areas of developing countries, usually by unskilled persons who do not have proper knowledge of the anatomy of reproductive organs and in unhygienic environments thus leading to various complications. Case presentation We discuss the case of a 21 year old female who presented in septic shock after she underwent an unsafe abortion of an 11 weeks pregnancy with uterine wall perforation and bowel injury that required resection. Conclusion Unsafe abortion is an important public health problem which accounts for a significant cause of maternal mortality and morbidity in resource poor countries. A high index of suspicion of clandestine abortion with ensuing complications should prevail when faced with a woman of child bearing age with the triad of vaginal bleeding, amenorrhea and pelvic sepsis.